Olanzapine-Associated Pisa Syndrome in an Autistic Adolescent. Issue 2 (March 2020) - Guler, Hasan Ali; Turkoglu, Serhat; Cetin, Fatih Hilmi; Ucar, Halit Necmi; Erdogan, Yakup
Abstract : Objectives: The objective of this study is to report a case of Pisa syndrome due to olanzapine use in an autistic adolescent. Methods: The patient was a 12-year-old adolescent girl who was taking olanzapine for autism-related behavioral problems. Abnormal posture and balance problems appeared in the third month of olanzapine treatment. The patient was diagnosed as having Pisa syndrome after clinical evaluation. Biperiden was started on the patient whose complaints continued despite olanzapine treatment was stopped. Patient's complaints regressed with biperiden treatment. Results: According to our knowledge, there is no an autistic adolescent case of Pisa syndrome previously reported in the literature. Further studies are needed to clarify the etiology and treatment of Pisa syndrome. Conclusions: In patients with balance problems and abnormal posture as a result of olanzapine use, the clinician should keep in mind Pisa syndrome.